Impact of intravenous administration of nalbuphine at different time points for postoperative analgesia and sedation in adenotonsillectomized children: a prospective, randomized controlled trial - Jinjin Huang; Jing Gao; Hongmin Cao; Chunying Bao; Haiya Tu; Qixing Chen (BMJ Publishing Group, 2023)
Objective To compare the efficacy of intravenous administration of nalbuphine at different time points for postoperative analgesia and sedation in adenotonsillectomized children.Methods Patients with obstructive sleep apnea syndrome scheduled for adenotonsillectomy were randomly divided into group A (patients received intravenous nalbuphine 0.2 mg/kg before anesthesia induction), group B (patients received intravenous nalbuphine 0.2 mg/kg 10 min before the end of surgery), and group C (patients did not receive nalbuphine injection). The time points for measuring outcomes were before anesthesia induction (T0), extubation (T1), and 0, 15, 30, or 45 min in the postanesthesia care unit (PACU) (T2-T5, respectively).Results There were 40 patients in group A, 41 patients in group B and 39 patients in group C. Patients in group B had significantly lower FLACC (Face, Legs, Activity, Cry, Consolability) pain scores at T2-T5 than those in group C (all p<0.05). Patients in group B had higher Ramsay Sedation Score at T2-T4 than those in group C (all p<0.05). The proportion of patients who received remedial analgesia in the PACU in group A (17.5%, p=0.008) and group B (9.8%, p<0.001) was significantly lower than that in group C (46.2%).Conclusion Intravenous administration of nalbuphine 10 min before the end of adenotonsillectomy in children could decrease pain intensity and increase sedation levels during the recovery period with the reduction of remedial analgesia in the PACU.Trial registration number ChiCTR2200060118.